ҲАРБИЙ ХИЗМАТЧИЛАРНИНГ ПЕДАГОГИК МАДАНИЯТИНИ ШАКЛЛАНТИРИШНИНГ АЙРИМ ЖИҲАТЛАРИ - Ходиев, Р.Х.; Саидбоев, Б.Ж. (SCIENCE and SOCIETY, 2020)
The article deals with some issues of forning pedagogical and professional culture in teaching military people. The author pays much attention to the role of pedagogical culture in teaching military people professional thinking, culture of speech, service ethics, pedagogical intuition, communication culture, professional-moral culture, culture of appearance and pedagogical skill.